A vision-based measurement installation for programmable logic controllers - Aydogmus, Omur; Talu, Muhammed F. (Elsevier Sci Ltd, 2012)
A vision-based measurement system is presented to obtain an economic installation for control and observe more than one process variables in industrial applications by using a Programmable Logic Controller (PLC) powered via Object Linking and Embedding for Process Control (OPC) technology. The proposed measurement system consists of a PLC, a simple webcam and a Supervisory Control and Data Acquisition (SCADA) PC. The proposed system is performed by using a pressure test bench to show performance of traditional and proposed measurement installations for an industrial PLC in real-time operation. The trend views of measured variables are compared at the same conditions and discussed in terms of price for one process variable. (C) 2012 Elsevier Ltd. All rights reserved.
Keywords: Industrial measurement; Dial gauge; Image processing; PLC; SCADA systems